2021
DOI: 10.1111/rode.12800
|View full text |Cite
|
Sign up to set email alerts
|

How climate change leads to emigration: Conditional and long‐run effects

Abstract: We study the effect of climate change on migration from 121 developing and emerging countries to 20 OECD countries between 1980 and 2010. In contrast to earlier studies, we differentiate between low‐ and high‐skilled migrants to account for the fact that not all groups are equally vulnerable and responsive to climate change. This is also the first study that uses a long‐difference approach. That is, in contrast to earlier studies that investigate short‐term weather changes or weather‐related disasters, we also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…The International ow of climate migrants cluster comprises studies that focus on measuring the environmental in uence on migration patterns. Most papers in this cluster adopt a quantitative approach (78%) with an international scope (68%), aiming to explain and predict the impact of climate variability on migration dynamics, along with its social and economic consequences [50][51][52] .…”
Section: Description Of Topicsmentioning
confidence: 99%
“…The International ow of climate migrants cluster comprises studies that focus on measuring the environmental in uence on migration patterns. Most papers in this cluster adopt a quantitative approach (78%) with an international scope (68%), aiming to explain and predict the impact of climate variability on migration dynamics, along with its social and economic consequences [50][51][52] .…”
Section: Description Of Topicsmentioning
confidence: 99%
“…Migration induced by climate change was also studied by Helbling & Meierrieks (2021). The dataset included 121 origin countries and 20 OECD destination countries for the interval of time 1980-2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Migration and climate change have become two of the most salient political and social issues over the last decades, with research on their relationship now abundant. While some studies find that climate change influences migration flows [1], others either do not [2] or reveal just indirect effects [3,4]. Recent meta-analyses by [5][6][7] have shown that most studies find that effects are dependent on specific contexts.…”
Section: Introductionmentioning
confidence: 99%